EFFECT OF FEAR OF SUCCESS ON EMPLOYEE CAREER DEVELOPMENT WITH ACHIEVEMENT MOTIVATION AS A MODERATING VARIABLE AT PT. PLN (PERSERO) BULUKUMBA AREA - Suhartini, Eka; Milawati, S; hardin, hardin (Institute for Research and Community Service, 2019)
Career development that makes others give different views such as appreciation, recognition, appreciation and higher social status in the eyes of society. This is what makes a person want to develop. But they are confronted with the reality that makes it negative. Require success or goals to be achieved and make someone doubt the ability required to fear success. This study aims to determine the effect of fear of success on career development and interaction on achievement motivation and fear of success on career development. This type of research is quantitative with associative research. The population in this study are companies that work at PT. PLN (Persero) Bulukumba Area. The technique of taking samples uses the saturated sample method. The sample in this study was 70 respondents. Data analysis uses simple linear regression analysis and moderation regression analysis by obtaining approved difference values. The results of research with simple linear regression show a fear of positive and significant success in career development. Analysis of moderating variables with the difference in assessment proves achievement motivation is not able to moderate the fear of success in career development.